Electrically Pumped Whispering Gallery Mode Lasing from Au/ZnO Microwire Schottky Junction. Issue 12 (4th September 2016) - Bashar, Sunayna B.; Wu, Chunxia; Suja, Mohammad; Tian, Hao; Shi, Wenhao; Liu, Jianlin
Abstract : Au/ZnO microwire Schottky diodes are fabricated. The devices exhibit typical Schottky diode I – V behavior with a turn‐on voltage of about 0.72 V. The hexagonal ZnO microwires act as whispering gallery mode (WGM) lasing microcavities. Under forward bias, a three‐microwire device exhibits WGM ultraviolet lasing spectra with a quality factor of about 1287. Output power of the laser has been measured at various injection currents, indicating threshold behavior with a threshold current of about 59 mA. Due to limited hole injection in the operation of Schottky diode, the lasing is a result of an excitonic recombination within the WGM cavity. Abstract : An electrically pumped whispering gallery mode laser diode based on Au–ZnO microwire Schottky junction is demonstrated. Typical Schottky behavior is achieved from this laser device and a moderate quality factor is reported. Exciton recombination is believed to be the mechanism of lasing generation. The new laser device structure provides an alternative approach toward semiconductor micro/nanolasers.